2012
DOI: 10.1007/s10238-012-0191-8
|View full text |Cite
|
Sign up to set email alerts
|

Significantly higher procalcitonin levels could differentiate Gram-negative sepsis from Gram-positive and fungal sepsis

Abstract: Procalcitonin (PCT) levels can distinguish between infectious and non-infectious systemic inflammatory response. However, there are some differences between Gram-negative (G-), Gram-positive (G+), and fungal bloodstream infections, particularly in different cytokine profiles, severity and mortality. The aim of current study was to examine whether PCT levels can serve as a distinguishing mark between G+, G-, and fungal sepsis as well. One hundred and sixty-six septic patients with positive blood cultures were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
100
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 14 publications
10
100
1
5
Order By: Relevance
“…There might be two reasons affecting the PCT level in patients with bacterial infection. First, the PCT level in patients with Gram-positive bacterial infections is much lower than that in patients with Gram-negative bacterial infections [19]. Second, inflammatory mediators such as IL-1β, tumor necrosis factor α and IL-6, which could elevate serum PCT levels in some elderly patients, especially those with poor immune response and those with local infections in early stages, might not be induced as soon as bacterial colonization [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…There might be two reasons affecting the PCT level in patients with bacterial infection. First, the PCT level in patients with Gram-positive bacterial infections is much lower than that in patients with Gram-negative bacterial infections [19]. Second, inflammatory mediators such as IL-1β, tumor necrosis factor α and IL-6, which could elevate serum PCT levels in some elderly patients, especially those with poor immune response and those with local infections in early stages, might not be induced as soon as bacterial colonization [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Also Brodska et al [40] stated that plasma PCT levels can be influenced by multiple factors such as individual genetically determined immune alert as well as the degree and type of microbial aggression or the extent of inflammation. The result of researcher, demonstrated that PCT has emerged as a biomarker for bacterial infections because it correlates with the extent and severity of microbial invasion in different infections [41].…”
Section: Table 2 Types and Profiles Of Organisms Isolated In 83 Patimentioning
confidence: 99%
“…20 Results using serum markers for diagnosing sepsis are often similar for gram-negative and gram-positive infections. 21 We detected specific demethylation of The relationship of partial methylation at -769 CpG, demethylation of 8 CpGs, demethylation of 7 CpGs, and -771 C:G > T:A; 5′ de novo -778 CpG mutation on both alleles to a bacterial infection is underlined by the fact that none of the controls showed these methylation changes, thus implying that they could serve as classical epigenetic infection markers. Moreover, samples collected prior to a LOS episode showed none of these methylation changes, while blood samples collected during LOS episodes showed partial methylation at -769 CpG.…”
Section: Discussionmentioning
confidence: 99%